Exploration of the Adsorption Kinetics of Surfactants at the Water-Oil Interface via Grand-Canonical Molecular Dynamics Simulations - Yang, Xue-Dan (Langmuir : the ACS journal of surfaces and colloids, 2022)
It is well-known that surfactants tend to aggregate into clusters or micelles in aqueous solutions due to their special structures, and it is difficult for the surfactant molecules involved in the aggregation to move spontaneously to the oil-water interface. In this article, we developed a new grand-canonical molecular dynamics (GCMD) model to predict the saturated adsorption amount of surfactant with constant concentration of surfactant molecules in the bulk phase, which can prevent surfactants aggregating in the bulk phase and get the atomic details of the interfacial structural change with increase of the adsorption amount through a single GCMD run. The adsorption of anionic surfactant sodium dodecyl sulfate (SDS) at the heptane-water interface was studied to validate the model. The saturated adsorption amount obtained from the GCMD simulation is consistent with the experimental results. The adsorption kinetics of SDS molecules during the simulation can be divided into three stages: linear adsorption stage, transition adsorption stage, and dynamic equilibrium stage. We also carried out equilibrium molecular dynamics (EMD) simulations to compare with GCMD simulation. This GCMD model can effectively reduce the simulation time with correct prediction of the interfacial saturation adsorption. We believe the GCMD method could be especially helpful for the computational study of surfactant adsorption under complex environments or emulsion systems with the adsorption of multiple types of surfactants